Combined effects of Deepwater Horizon crude oil and environmental stressors on Fundulus grandis embryos. (4th June 2018) - Rodgers, Maria L.; Jones, Elizabeth R.; Klinkhamer, Christopher; Mahapatra, Cecon T.; Serafin, Jennifer; Bosker, Thijs; Perkins, Christopher; Griffitt, Robert J.; De Guise, Sylvain; Sepúlveda, Maria S.
Abstract: In the present study, we examined how sensitivity to oil changes in combination with environmental stressors in Fundulus grandis embryos. We exposed embryos (<24 h post fertilization) to a range of high‐energy water accommodated fraction (HEWAF) concentrations (0–50 parts per billion [ppb] total polycyclic aromatic hydrocarbons [PAHs]) made from Macondo crude oil in conjunction with various environmental conditions (temperature: 20 and 30 °C; salinity: 3, 7, and 30 practical salinity units [PSU]; and dissolved oxygen: 2 and 6 mg/L). Endpoints included mortality, hatching rates, and expression of cytochrome p450 1a and 1c ( cyp1a, cyp1c ) in hatched larvae. There was 100% mortality for all fish under the 2 parts per million (ppm) dissolved oxygen regimes. For the 6 mg/L dissolved oxygen treatments, mortality and median lethal time (LT50) were generally higher in the 30 °C treatments versus the 20 °C treatments. Oil increased mortality in fish exposed to the highest concentration in the 20‐3‐6 (°C‐PSU‐mg/L), 25‐7‐6, and 30‐30‐6 conditions. Hatching was driven by environmental conditions, with oil exposure having a significant impact on hatching in only the 25‐7‐6 and 30‐30‐6 groups at the greatest HEWAF exposure. Expression of cyp1a was up‐regulated in most treatment groups versus the controls, with cyp1c expression exhibiting a similar pattern. These data suggest interactive effects among temperature, salinity, and PAHs, highlighting a need to further assess the effects of oil exposure under various environmental conditions. Environ Toxicol Chem 2018;37:1916–1925. © 2018 SETAC